Social Support and Emotional Intelligence as Protective Resources for Well-Being in Moroccan Adolescents - Lopez-Zafra, Esther; Ramos-Álvarez, Manuel Miguel; El Ghoudani, Karima; Luque-Reca, Octavio; Augusto-Landa, José María; Zarhbouch, Benaissa; Alaoui, Smail; Cortés-Denia, Daniel; Pulido-Martos, Manuel (Frontiers in Psychology, 2019)
This study aimed to test a structural model to examine the protective role of psychosocial variables, such as social support, emotional intelligence and their interaction, on the cognitive dimension of subjective positive well-being (life satisfaction) and negative well-being (depression) in Moroccan adolescents. The participants consisted of 1277 students (571 men, 694 women and 12 missing values) with a mean age of 16.15 years (SD = 2.22; range = 9 to 23) who attended twenty-six public schools in different territories of Morocco. These students were in secondary education (n= 893) and high school (n= 378). The scales for measuring the variables of interest had to be adapted and validated as a previous step for the further proposal of a model of relations. Statistical analyses were conducted using structural equation modeling (SEM) to test the proposed model. The model that optimally adjusted the data confirmed the protective role of social support in the well-being of Moroccan adolescents. Consistent with previous studies, social support was directly related to well-being. However, it also indirectly affected levels of satisfaction with life. Likewise, the inclusion of emotional intelligence as an additional protective factor contributed to the explanation of the well-being mechanisms in adolescents. In addition to direct associations with the levels of social support, satisfaction with life and depression (negative in the latter case), emotional intelligence contributed to the explanation of depression through its effects on life satisfaction. Moreover, the interaction of emotional intelligence with social support was confirmed to determine levels of life satisfaction in adolescents. Specifically, social support multiplied the effects of the relationship between satisfaction with life and emotional intelligence in cases of moderate and high levels in Moroccan adolescents. This study fills a gap in the literature by adapting and further analyzing several scales with Moroccan samples of adolescents and by proposing and verifying a relational model that can help researchers and teachers to more precisely clarify these relations according to their context. The enhancement of protective factors, such as social support and emotional intelligence, will promote healthy youth development, thus creating healthier societies in the future.